Hepatitis C Pretreatment Profile and Gender Differences: Cognition and Disease Severity Effects - Barreira, David Pires; Marinho, Rui Tato; Bicho, Manuel; Flores, Isabel; Fialho, Renata; Ouakinin, Sílvia (Frontiers in Psychology, 2019)
Background: The hepatitis C virus (HCV) is known to infect the brain, however, findings on associated neuropsychiatric syndrome are controversial and the association itself remains unclear. Gender research in HCV infection is limited, failing to integrate the role of gender differences on neurocognitive syndrome. The aim of this study was to characterize psychological and neurocognitive profiles in HCV-infected patients before treatment and to explore gender differences in those profiles, as well as, the impact of disease severity. Methods: A total of 86 patients diagnosed with chronic hepatitis C were included. Depresson and anxiety were assessed using Hamilton anxiety scale (HAM-A), Hamilton depression scale (HAM-D), Beck Depression Inventory (BDI) and for cognition a neuropsychological battery to measure attention, concentration, memory and executive functions components validated for the Portuguese population was used, before starting treatment. To identify the disease severity, platelet ratio index and FibroScan were used. Results: A statistically significant gender effect was found on HAM-A (B = 0.64, CI: 0.17-1.11) and HAM-D (B = 0.62, CI: 0.14-1.09), with women scoring higher compared to men. Regarding neuropsychological scores, significant differences between gender were identified in executive functions measured by Trail Making Test (TMT B) (B = 0.48, CI: 0.02-0.97), TMT B-A (B = 0.26, CI: -39.2 to -3.7) and in digit span total (B = -0.52, CI: -1.0 to -0.04), with women performing worse than men. Controlling for years of substance dependence, TMT-B and TMT B-A showed significant gender differences. Regarding the presence or absence of substance dependence, only HAM-A and HAM-D remained significant. For categorical variables, Digit Span Total was also influenced by gender, with women being more likely to be impaired: odds ratio (OR) = 7.07, CI: 2.04-24.45), and a trend was observed for Digit Span Backward (OR = 3.57, CI: 1.31-9.75). No significant differences were found between disease severity and neurocognitive performance. Conclusion: Data suggest that gender has an influence on depression, anxiety and cognitive functions with women showing more impairment when compared with men. This effect seems to be influenced by substance dependence.